Exploring the Principles of GC-MS: Techniques and Applications - Khalifea, Hassan; Ali, Noor (Indonesian Journal Publisher, 2025)
GC-MS operates as a robust analytical method that chemistry labs commonly use because it effectively separates chemicals while identifying their components with precise accuracy. Research instruments like GC-MS provide high quality separation and molecular identification which makes them indispensable for environmental studies as well as pharmaceutical insights and forensic investigations and quality control applications. Extensive usage of GC-MS remains incomplete because researchers must develop an organized framework which illustrates system elements and their supporting functions together with application boundaries. The main objective of this research is to establish a systematic examination of GC-MS core functioning and equipment alongside examining operational details and system constraints. The research shows how GC-MS components including injectors, columns, ionization techniques, mass analyzers and detectors function together to achieve optimal performance results. The research presents current uses of GC-MS in environmental monitoring and pharmaceutical analysis and forensic science through methodological examples while supplying reference spectra. This comprehensive study combines GC-MS principles with practice to provide a unified framework which includes reviews regarding recently developed hyphenated methods and ionization approaches and column development. The research results function as a useful guide for scientists as well as practitioners to help them select systems properly and develop methods and advance GC-MS systems for intricate analytical tasks.